A SEMIOTICS OF VISUAL IN DOUBLE BLIND MOVIE - Afritiansyah, Dhea Anggy (LINGUA LITERA : journal of english linguistics and literature, 2024)
Visual Semiotics is a new branch of semiotics that analyzes how visual signs or visual imagesconvey messages. In Visual semiotics, signs can be words, sounds, or visual images. Themovie of the double blind is one of the categories of visual semiotics. The movie consists ofimages by using visual semiotics analysis, this research aims to identify the signs containedin Double blind movie and how the signs are interpreted. The movie Double blind as theresearch data was collected using visual qualitative, the data was analyzed using visualsemiotics with the theory proposed by Charles Sanders Pierce. This research uses descriptivequalitative data analysis as the research method. The research results show that there is visualsemiotics based on the theory of Charles Sanders Pierce in the movie Double blind (2023).Analyze the data on the object, this research uses semiotic analysis techniques according toCharles Sanders Pierce. Based on this, it can be concluded that the movie Double Blind(2023) can be matched with Charles Sanders Pierce's semiotic theory.